Prediktor Kekambuhan Tuberkulosis di Kabupaten Bantul Yogyakarta 2014 - Nooria Sukmaningtyas; Ning Rintiswati; Riris Andono Ahmad (Berita Kedokteran Masyarakat (BKM), 2016)
Predictors of tuberculosis recurrence in the district of Bantul PurposeThe purpose of this research was to identify associated factors of TB recurrence. MethodsThe study design was a retrospective cohort. We  used TB cases registered in Bantul regency data in 2003-2014 that consisted of 3418 patients. Sampling was conducted by non-random methods with purposive sampling based on inclusion criteria of 904 samples. The variables measured were: age, sex, drug swallowing supervisor, health service facility, socioeconomic and sputum conversion. We used the Cox proportional hazard model for data analysis to determine the rate of occurrence and timing of the occurrence of an event. ResultsMale sex (HR = 0.91; p-value = 0.17) age> 40 years (HR = 1.03; p-value = 0.59), low income (HR = 0.89; p-value = 0.11) were not predictors of TB recurrence, while hospital treatment (HR = 0.81; p-value = 0.00), no sputum conversion (HR = 0.58; p-value = 0.00), treatment failure (HR = 0.49; 95% CI: 0.37-0.64), and treatment of less than 6 months (HR = 0.008; 95% CI: 0.00-0.07) were predictors of TB recurrence. There were 56 (6.18%) of 904 patients who experienced relapse after cured or failed treatment. The average patient relapsed after 17 months of completion of the first treatment. ConclusionHealth facilities, sputum conversion, end-of-treatment status and duration of treatment are pulmonary TB recurrence factors, and as a result can be used to predict TB recurrence in the district of Bantul.